Gap in the Mastery of ICT Soft Skills for Vocational Graduate Workers in Industry: Case Study of LPP Polytechnic - Harjanti, Ratna Sri; Puspasari, Dyah; Hidayat, Arif; Purnomosidi, RY Kun Haribowo; Andari, Yuni; Bagaskara, Bagaskara; Romadona, Mia Rahma; Setiawan, Sigit; Budiansyah, Andi; Fachrizal, Fachrizal; Helmi, Rahmi Lestari; Suryadi, Suryadi; Maulana, Syahrizal; Tsuraya, Silmi (STI Policy and Management Journal, 2023)
The COVID-19 pandemic has forced a global shift toward technical and inventive skills to improve job readiness and productivity. Human resources graduates from diploma levels 3 and 4 must respond with has competitively by adding value from soft skills. This can help them compete in domestic and international job markets. These skills are now required for professional acceptance. This study investigates the role of soft skills in learning and using information technology, the internet, and computers to boost individual and organizational efficiency. This study addresses all research questions and objectives using a combination of methods. We collected quantitative data on technology and innovation mastery ability gaps using online surveys. Comprehensive interviews with educational institutions, government agencies, industry representatives, and vocational diploma level 3 and 4 alumni were also conducted for the study. The data showed no statistically significant difference in alumni' technological proficiency between when they study and when they work. This shows that many former students have learned to use soft skills to boost their professional competitiveness and technical ability. ICT skills improve vocational human resources' employability, making them more competitive and competitive with undergraduate graduates. Keywords: Vocational, Soft Skill, Technology, Competencies, productivity, competitiveness